2002
DOI: 10.1042/bj3630761
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cell growth through inactivation of eukaryotic translation initiation factor 5A (eIF5A) by deoxyspergualin

Abstract: The mechanism of inhibition of cell growth by deoxyspergualin was studied using mouse mammary carcinoma FM3A cells. Results of studies using deoxyspergualin analogues showed that both the guanidinoheptanate amide and glyoxyspermidine moieties of deoxyspergualin were necessary to cause inhibition of cell growth. When deoxyspergualin was added to the medium, there was a strong inhibition of cell growth and formation of active eukaryotic translation initiation factor 5A (eIF5A) at the third day of culture. There … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Because its expression is elevated in growing cells, it has been implicated in cell proliferation (Gorlach et al, 1994). The gene product of eIF5A has also been implicated in cell viability and cell proliferation (Nishimura et al, 2002;Park et al, 2003). The hair matrix is considered to be occupied by ''transient amplifying'' cells that proliferate constantly during anagen (Paus et al, 1994;Xu et al, 2003).…”
Section: Figurementioning
confidence: 97%
See 1 more Smart Citation
“…Because its expression is elevated in growing cells, it has been implicated in cell proliferation (Gorlach et al, 1994). The gene product of eIF5A has also been implicated in cell viability and cell proliferation (Nishimura et al, 2002;Park et al, 2003). The hair matrix is considered to be occupied by ''transient amplifying'' cells that proliferate constantly during anagen (Paus et al, 1994;Xu et al, 2003).…”
Section: Figurementioning
confidence: 97%
“…Cathepsin E was expressed in the cuticle of the keratogenous zone. Poly-A-binding protein (PABP)/cytoplasmic 1 (Sachs et al, 1986;Afonina et al, 1998;Deo et al, 1999) and eukaryotic translation initiation factor 5 (eIF5A) (Nishimura et al, 2002) were expressed in germinative hair matrix cells. Cytokeratin 12 was detected in the inner root sheath of the hair bulb.…”
Section: Figurementioning
confidence: 99%
“…In the second reaction, deoxyhypusine hydroxylase (DOHH) converts the deoxyhypusine-containing intermediate to the hypusine-containing mature eIF5A. This hypusination of eIF5A is critical not only for the proliferation of eukaryotic cells but also for the regulation of protein translation of selected mRNA that are associated with the synthesis of oncoproteins and thus enhances the proliferation of tumor cells. , In addition, a recent publication has reported that eIF5A is involved in cellular respiration and macrophage function by regulating mitochondrial proteins, which can be linked to cancer cell metabolism . Therefore, blocking the biological activity of eIF5A by inhibiting the DHPS-mediated hypusine modification of the eIF5A precursor protein may be a useful strategy that can be employed in the treatment of tumorigenic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Both the guanidinoheptanoylamide and glyoxyspermidine fragments are necessary for the exertion of this effect. The level of inhibition of the cellular growth is similar in five compounds (LXXX) and (LXXXII)-(LXXXV), whereas the analogue without guanidine group (LXXXVI) and the individual compounds ω-guanidinoheptanoylamide (LXXXVII) and N- [4-(3-aminopropylamino)butyl]-2,2-dihydroxyacetamide (LXXXVIII) do not have such properties [58].…”
Section: Biological Activity Of Metabolites Of Microorganisms and Thementioning
confidence: 99%